Avaliação do adjuvante Advax na formulação de vacina de subunidade proteica contra Mycobacterium tuberculosis - Santos, Bruno de Paula Oliveira (2017)
Tuberculosis is an infectious disease caused mainly by the bacteria Mycobacterium tuberculosis. The only way to prevent is to vaccinate with BCG, an attenuated Mycobacterium bovis strain. However, the vaccine has variable efficacy in different people and it does not protect adults. The aim of this study was to develop new subunit vaccine formulations, evaluating a new adjuvant: Advax and two recombinant fusion proteins: CMX and ECMX. To formulate the subunit vaccines three adjuvants were used: the Advax3, Advax4 and CpG-DNA. First we addressed the CMX protein. BALB/c mice were separated in experimental groups that received 3 doses of the vaccines, besides the control groups (Saline, BCG, CMX, Advax3 and Advax4). The vaccines induced increase the local inflammatory response and they were able to activate blood and lymphatic endothelial cells on draining lymph nodes. After the first dose, the mice vaccinated with Advax3 + CMX, Advax4 + CMX and CpG-DNA + CMX generate IgG2a humoral immune response. After the second dose, the vaccinated mice also induced an IgG1 response. After challenging with M. tuberculosis and after 45 days, the vaccines BCG, Advax3 + CMX, Advax4 + CMX and CpG-DNA + CMX showed specific Th1 responses. However, the Th17 cellular response was not observed. Evaluating the lung lesions induced by the infection, Advax4 + CMX group presented reduced inflammatory cell infiltrate and maintenance on the pulmonary architecture. The vaccines Advax3 + CMX e Advax4 + CMX were able to extend the animals life, but none, except the BCG, were able to reduce the bacillary load on the lungs of infected mice, forty five or ninety days after the challenge. To improve the vaccine, ECMX was tested with Advax4. This vaccine showed similar humoral and cellular responses and reduced M. tuberculosis bacillary load. The vaccine formulations developed were immunogenic and the formulations containing Advax4 + ECMX were more effective and may be tested as vaccine against tuberculosis.